Penetapan Kadar Vitamin C Buah Nanas Segar (Ananas comocus L.) Hasil Budidaya di Kecamatan Teluk Meranti, Kabupaten Pelalawan dengan Metode Spektrofotometri UV-Vis - Annisa Fauzana (LPPM Universitas Abdurrab, 2022)
Vitamin C is a water-soluble antioxidant that affect the body immune system. Vitamin C deficiency is related to the high risk of infection disease manifestation. Consuming vitamin C of 100-200 mg/day is effective to optimize physiological functions of tissues and cells. Fruits are a natural source of vitamin C that can be consume to achieve vitamin C requirement intake, such as Ananas comocus. However, the vitamin C content in Ananas comocus can be varied depending on some factors, such as their varieties, growth environment, and preparation. This research aims to determine vitamin C content in some fresh Ananas comocus fruits from three plantations in Teluk Meranti area, Pelalawan using Spectrophotometry UV-Vis method, that is a suitable method for vitamin C content determination. The result shows that the calibration curve of vitamin C giving a good linearity, with r value of 0,9943. Vitamin C content in the three plantation was varied. The content from the plantation 1, 2, and 3 was 51,1889; 48,3320; dan 144,200 mg/100 g. Keywords: fresh fruit, spectrophotometer, vitamin C content determination, Teluk Meranti, Ananas comocus